Therapeutic and Pharmacological Properties of Pumpkin Seeds: A Comprehensive Review - Silky; Bisla, Gita; Srishti (Journal for Research in Applied Sciences and Biotechnology, 2024)
A well-known edible plant in the Cucurbitaceae family, the pumpkin has long been utilized as a functional meal or a herbal remedy. Pumpkin seeds are rich in phytoestrogens, vitamin E, and unsaturated fatty acids, which may have medicinal and nutraceutical uses. The use of pumpkins in traditional medicine to treat a wide range of conditions, including inflammation, dyslipidemia, bacterial or fungal infections, malignancies, intestinal parasites, hypertension, arthritis, and hyperglycemia, has drawn attention to the need for additional study on both the fruits and seeds of the pumpkin plant. Proteins, antioxidative phenolic compounds, tocopherols, triterpenes, saponins, phytosterols, lignans, and carotenoids are some of the micro- and macro-constituent compositions that improve pumpkin seeds. Pumpkin seeds have antidepressant properties and are mostly used in the management of benign prostatic hyperplasia (BHP). Regular pumpkin seed eating lowers the risk of Parkinson's and Alzheimer's disease. Since pumpkin seeds are high in tocopherols, they can be extracted for edible oil and then used to formulate other foods at a later time. The pharmacological effects of pumpkin seeds have made them quite popular. Additionally, pumpkin seed oil has numerous health advantages. Pumpkin seeds are mostly composed of unsaturated fatty acids, which have been shown to provide potential health benefits and to prevent disease. Although pumpkin seeds are clearly very useful, their full potential has not yet been discovered.